2017
DOI: 10.1111/vcp.12498
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic features of a feline inductive odontogenic tumor

Abstract: The feline inductive odontogenic tumor (FIOT) is a rare entity among oral tumors in cats, the cytologic features of which are not well characterized but may prove useful. A fine-needle aspiration biopsy was performed on the right mandible between the permanent canine (404) and permanent fourth premolar (408) of an 8-month-old female mongrel cat. Cytologic smears showed epithelial cells and occasional spindle cells with extracellular homogenous acidophilic material in a hematic background. The initial diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Also, previous studies have mostly reported short-term follow-ups after surgical treatment (4,7,12). In this study, three cases of FIOT were presented to the veterinary hospital for specialized dentistry to assess and treat oral tumors from October 2015 to August 2018.…”
mentioning
confidence: 99%
“…Also, previous studies have mostly reported short-term follow-ups after surgical treatment (4,7,12). In this study, three cases of FIOT were presented to the veterinary hospital for specialized dentistry to assess and treat oral tumors from October 2015 to August 2018.…”
mentioning
confidence: 99%